A Comparison of the Effect of Decorsin and Two Disintegrins, Albolabrin and Eristostatin, on Platelet Function - McLane, Mary Ann; Gabbeta, Jagadeesh; Rao, A Koneti; Beviglia, Lucia; Lazarus, Robert A; Niewiarowsk, Stefan (Thrombosis and Haemostasis, 1995)
Naturally-occurring fibrinogen receptor antagonists and platelet aggregation inhibitors that are found in snake venom (disintegrins) and leeches share many common features, including an RGD sequence, high cysteine content, and low molecular weight. There are, however, significant selectivity and potency differences. We compared the effect of three proteins on platelet function: albolabrin, a 7.5 kDa disintegrin, eristostatin, a 5.4 kDa disintegrin in which part of the disintegrin domain is deleted, and decorsin, a 4.5 kDa non-disintegrin derived from the leech Macrobdella decora, which has very little sequence similarity with either disintegrin. Decorsin was about two times less potent than albolabrin and six times less potent than eristostatin in inhibiting ADP- induced human platelet aggregation. It had a different pattern of interaction with glycoprotein IIb/IIIa as compared to the two disintegrins. Decorsin bound with a low affinity to resting platelets (409 nM) and to ADP-activated platelets (270 nM), and with high affinity to thrombin- activated platelets (74 nM). At concentrations up to 685 nM, it did not cause expression of a ligand-induced binding site epitope on the (β3 subunit of the GPIIb/IIIa complex. It did not significantly inhibit isolated GPIIb/IIIa binding to immobilized von Willebrand Factor. At low doses (1.5-3.0 μg/mouse), decorsin protected mice against death from pulmonary thromboembolism, showing an effect similar to eristostatin. This suggested that decorsin is a much more potent inhibitor of platelet aggregation in vivo than in vitro, and it may have potential as an antiplatelet drug.